Evaluation of Public Services At the Bodor Village Office, Nganjuk Regency - Yanuarita, Heylen Amildha (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The village government has tasks including improving the welfare of the community, maintaining peace and order in the community, implementing the principles of village governance that are clean and free from collusion and nepotism (KKN), and organizing good government administration. This is also the task carried out by the Bodor Village Office apparatus in Nganjuk Regency in providing services to the community. In order to determine the quality of public services at the Bodor Village Office in Nganjuk Regency, it is necessary to conduct public service evaluation research. This research method uses a qualitative approach that describes the quality of providing services to the public through interviews with informants, observation and documentation. The results showed that public services at the Bodor Village Office, Nganjuk Regency are quite good, but the services provided need to be improved, especially in terms of supporting facilities and infrastructure, supported by qualified human resources, responsive public service officers of the Bodor Village Office have readiness in providing services, besides that the Bodor Village community feels trust in public service officers because of the guarantee of timeliness of services as delivered, for the form of empathy from public service officers can be seen from the way they pay attention to people who want to get public services.